Biological management of sheath blight of rice - D.K. HAZARIKA, B.C. DAS and (Indian Phytopathology, 2002)
The influence of seed treatment of rice with two antagonistic fungi, Trichoderma viride and T. harzianum, alone and in association with 2% (w/v) methylcellulose and/or 0.1 M MgSO4 against sheath blight (Rhizoctonia solani) was studied under pot conditions during ahu season of March 1994-March 1995. The seeds treated with T. viride and T. harzianum showed significant reduction in sheath infection. Both antagonists exhibited higher efficacy in reducing sheath infection and increased grain yield whenthey were treated with either 2% (w/v) methylcellulose or 2% (w/v) methylcellulose and 0.1 M MgSO4. T. harzianum was more effective than T. viride in reducing sheath infection and increase in yield.